Progestin-primed ovarian stimulation with letrozole using different doses of medroxyprogesterone acetate per day: a retrospective cohort study - Li, Hai-long; Shen, Bei-bei; He, Zheng-liang; Wang, Hai-li; Sun, Zhi-feng (Frontiers in Endocrinology, 2024)
Background In the progestin-primed ovarian stimulation protocol, the oral administration of medroxyprogesterone acetate has been observed to effectively inhibit the LH surge during ovarian stimulation in patients experiencing infertility. Nevertheless, the use of utilizing medroxyprogesterone acetate during ovarian stimulation can result in more pronounced pituitary suppression, potentially necessitating increased doses of gonadotropins and extended treatment durations. Therefore, it is necessary to determine the optimal dose of medroxyprogesterone acetate, aiming to use relatively lower concentrations of medroxyprogesterone acetate to effectively and safely suppress early LH surges. Method This retrospective cohort study included 710 patients who underwent cycles of in vitro fertilization or intracytoplasmic sperm injection and were subjected the progestin-primed ovarian stimulation protocol utilizing letrozole between from 1st January 2021 to 31st December 2021. The study population was divided into low, medium, and high concentration groups based on the daily dosage of medroxyprogesterone acetate.The primary focus of this investigation was on the cumulative live birth rate. Secondary outcomes encompassed the occurrence of a premature surge in luteinizing hormone, the quantity of retrieved oocytes, viable embryos, and high-quality embryos, as well as clinical pregnancy rate, abortion rate, ectopic pregnancy rate, and multiple pregnancy rate. Results In this study, significant differences were observed among three groups in various parameters including body mass index, baseline levels of Anti-Müllerian hormone and luteinizing hormone, antral follicle count, total dose of gonadotropin, and duration of gonadotropin administration (p<0.05). The number of oocytes and viable embryos were significantly higher in medium group and higher than those in the low dose group. Following adjustments for confounding factors related to medroxyprogesterone acetate for various outcome measures, we conducted multiple regression analysis to investigate the independent effects of daily medroxyprogesterone acetate dosage within the combined progestin-primed ovarian stimulation and letrozole protocol. Following multivariable regression analysis, no disparities were found in embryo characteristics (number of oocytes retrieved, number of available embryos, number of high-quality embryos) or pregnancy outcomes (clinical pregnancy rate, cumulative live birth rate) among the three groups. Conclusion Progestin-primed ovarian stimulation with letrozole using different dose of medroxyprogesterone acetate per day was comparable in terms of the number of oocytes retrieved, the number of high-quality embryos, clinical pregnancy rate and cumulative live birth rate after frozen embryo transfer.